The Degree of Transformational Leadership for Education Managers and Its Relation to Motivation Among Workers in The Department of Education in Northern Governorates in Palestine from Workers’ Perception - Mohammad Muin Abdelrahim Ismael (My University, 2016)
The purpose of this study was to determine the degree of transformational leadership among education managers and their relation to motivation among workers in the departments of education in the northern provinces in Palestine from the viewpoint of its employees, in light of the independent variables of the study, namely: sex, age, educational qualification, experience, administrative labeled place housing, the researcher has followed the descriptive method Correlative approach to the study, and were selected by a stratified random sample representative of the number of employees in the departments of Education staff, as were distributed (404) to identify the study sample. Evidenced by the results of the study that the degree of transformational leadership among education managers in the northern provinces in Palestine from the viewpoint of its employees has been high with a mean amounted to (3.5) and standard deviation arrived (0.70), where the lowest paragraphs where the response is to topics concerning the participation of employees in the development of the objectives of the Directorate, and the organization of professional growth of staff meetings, and provide examples to help employees do their jobs, and provide ideas for the formation of a future vision for the development of civil society organizations, and encouraging employees to participate in decision-making, and work on the development of staff and empower them, and to actively participate in the build a consensus of opinion on the objectives of the Directorate, and provide new ideas for the institution. As evidenced by the results of the study that the degree of motivation of employees in the departments of Education in the northern provinces in Palestine from the viewpoint of their workers have arrived to an arithmetic mean was (3.8) and standard deviation came to 0.46), a high degree, either paragraphs that got the slightest response from the perspective of the respondents were represented subjects such as lack Tnawsp salary with the work, the lack of existence, the norms of a specific and fair performance evaluation, reduced the feeling that the Directorate gives opportunities for excellence and innovation, and low ease of access to everything he needs to do the work, and the lack of Directorate policy agreement with the convictions of staff Personal. Evidenced by the results of the study and the presence of correlation positive statistically significant between motivation inspirational, motivation, and this relationship is statistically significant because the value of sig = (0.00) as there are positive relationship between the individual mind and motivation and this relationship is statistically significant there is a positive relationship between the individual mind and motivation, and positive relationship between exist excitement and intellectual motivation and this relationship is statistically significant, as there is a positive relationship between the ideal influence and motivation and this relationship is statistically significant there is a positive relationship between the individual mind and motivation. the results of the study showed that there is a positive relationship between the practice of transformational leadership and motivation and this relationship is statistically significant there is a positive relationship, and the light of the results of the study have been put forward recommendations such as working on the development of transformational leadership skills of immediate superiors, in order to enhance the creative capabilities of their subordinates, the study of transformational leadership relationship and to enable workers in the civilian labor organizations in other societies Kalmassat government.

هدفت هذه الدراسة إلى التعرف على درجة ممارسة القيادة التحويلية لدى مديري التربية والتعليم، وعلاقتها بالدافعية لدى العاملين في مديريات التربية في المحافظات الشمالية في فلسطين، من وجهة نظر العاملين فيها، في ضوء متغيرات الدراسة المستقلة وهي: الجنس، والعمر، والمؤهل العلمي، والخبرة، والمسمى الإداري، ومكان السكن، وقد اتبع الباحث المنهج الوصفي الارتباطي منهجاً للدراسة، وقام باختيار عينة طبقية عشوائية ممثلة لعدد الموظفين العاملين في مديريات التربية والتعليم، إذ تم توزيع (404) استبانة على أفراد عينة الدراسة. تبين من نتائج الدراسة بأن درجة ممارسة القيادة التحويلية لدى مديري التربية والتعليم في المحافظات الشمالية في فلسطين من وجهة نظر العاملين فيها، كانت عالية بمتوسط حسابي بلغ (3.5) وبانحراف معياري وصل إلى (0.70). ويتضح من نتائج الدراسة بأن درجة الدافعية للعاملين في مديريات التربية و التعليم في المحافظات الشمالية في فلسطين من وجهة نظر العاملين فيها قد جاءت بمتوسط حسابي بلغ (3.8) وبانحراف معياري وصل إلى( 0.46) وهي درجة عالية. كما يتضح من نتائج الدراسة وجود علاقة ارتباطيه ايجابية دالة إحصائياً بين الحافز الإلهامي والدافعية وهذه العلاقة دالة إحصائياً لأن قيمة (0.00) ، كذلك توجد علاقة إيجابية بين الاعتبار الفردي والدافعية وهذه العلاقة دالة إحصائياً، توجد علاقة إيجابية بين الاعتبار الفردي والدافعية، كذلك توجد علاقة إيجابية بين الإثارة الفكرية والدافعية وهذه العلاقة دالة إحصائياً، كذلك توجد علاقة إيجابية بين التأثير المثالي والدافعية وهذه العلاقة دالة إحصائياً ، وقد بينت نتائج الدراسة بأنه توجد علاقة إيجابية بين ممارسة القيادة التحويلية والدافعية وهذه العلاقة دالة إحصائياً، وفي ضوء نتائج الدراسة تم طرح التوصيات، مثل: العمل على تنمية مهارات القيادة التحويلية لدى الرؤساء المباشرين، بغرض تعزيز القدرات الإبداعية لدى مرؤوسيهم، ودراسة علاقة القيادة التحويلية وتمكين العاملين في منظمات العمل المدني في مجتمعات أخرى كالمؤسسات الحكومية.
درجة ممارسة القيادة التحويلية لدى مديري التربية والتعليم وعلاقتها بالدافعية لدى العاملين في مديريات التربية في المحافظات الشمالية في فلسطين من وجهات نظر العاملين فيها